ETH Zurich’s university collections and archives in the digital age: innovative indexing, digitisation and publication of unique materials - Wiederkehr, Stefan (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2018)
ETH Zurich’s university collections and archives encompass around twenty facilities with unique holdings. Their diversity reflects the historic development of collections at the university and its modern potential for research and teaching. ETH Zurich makes its collections and archives available for research and teaching in a form that befits the digital age. To this end, it combines ETH Library’s skills in information science with the expertise of the collection owners in the departments in accordance with the Strategy 2015 to 2020, which was passed by the Executive Board in 2014. This paper presents the strategic approach of ETH Zurich’s Executive Board and focuses on the role of ETH Library in the current line of action.